HUBUNGAN PENGETAHUAN IBU, PEMBERIAN ASI EKSKLUSIF DAN WAKTU PEMBERIAN MAKANAN PENDAMPING ASI DENGAN STATUS GIZI BALITA DI DESA KEMBARAN - Dede Setiawan (LPPM ITEKES Mahardika, 2018)
Background: Nutrition is an important part of the body needs for growth and development of children. Childhood, especially toddler is a period of growth and development of the most rapidly. Toddler nutritional adequacy is depend on the child's mother. Lack of knowledge about nutrition will reduced ability to apply in everyday life, this is one of the causes of malnutrition in toddler. In addition, nutritional problems in toddler is also due to breastfeeding practices and complementary feeding was not appropriate in terms of both quantity and quality. Purpose: Objective of this research is to determine correlation between mother’s knowledge, exclusive breestfeeding and patterns time of complementary feeding with nutritional status of toddlers at Kembaran village, Kembaran district, Banyumas regency. Method: The research design use descriptive correlation with cross-sectional approach. Population in this study were all mothers who have toddlers age 6-24 months at Kembaran village as many as 148 people. Sampling technique use simple random sampling with 66 samples. Data analyze with Chi Square test. Instrumental research use questionnaires and nutritional status with weight/aged indicators. Result: There was significant correlation between mother’s knowledge (p value = 0,012), exclusive breastfeeding (p value = 0,039) and patterns time of complementary feeding (p value = 0,039) with the nutritional status of toddlers at Kembaran village. Conclusion: There was correlation between mother knowledge, exclusive breestfeeding and patterns time of complementary feeding with the nutritional status of toddlers. It is recommended to the toddler's mother to improve the quality of breastfeeding, complementary feeding and give breesfeeding to their babies up to 2 years in order to maintain the nutritional status who have been good status.